Effect of low‐energy ion impact on the structure of hexagonal boron nitride films studied in surface‐wave plasma. (8th November 2018) - Torigoe, M.; Kamimura, Y.; Teii, K.; Matsumoto, S.
Abstract : A high‐density surface‐wave plasma source is used to deposit hexagonal boron nitride (hBN) films in a gas mixture of He, H2, N2, Ar, and BF3 under a high ion flux condition using low‐energy ion irradiation. The ion energy is controlled between around zero and 100 eV by applying a negative or positive bias voltage to a substrate, while the ion flux is increased by locating a substrate upstream in the diffusive plasma. For ion energies above ∼37 eV, the structure of the films depends upon ion energy more than substrate temperature, typical of subplantation processes. As a result, the structural order and crystallinity of sp 2 ‐bonded phase in the films characterized by Fourier transform infrared spectroscopy and X‐ray diffraction are increased with decreasing ion energy, while the mass density of the films characterized by X‐ray reflectivity is retained relatively high with a slight dependence upon ion energy.